Are irrigation projects in Sub-Saharan Africa prohibitively expensive?: Evidence from new data and insights for future investments - Inocencio, Arlene B.; Maruyama, Atsushi; Tonosaki Manabu; Merrey, Douglas J.; Kikuchi, Masao (2007)
This paper uses 314 irrigation projects implemented from 1960-2000 in six regions worldwide to identify: (1) whether the perception of high cost of irrigation projects in SSA can be empirically supported; (2) what factors determine the costs and performance of irrigation projects; and (3) whether there are cheaper and better performing irrigation investments for SSA. This study shows that the popular view that African irrigation projects are prohibitively expensive is not tenable, and demonstrates that there are viable investment options for irrigation development in SSA.